An electron transport complex required in the gut sensitizes Bacteroides to a pore-forming type VI secretion toxin - Hannah K. Ratner; Brandon D. Duong; Pengrui Miao; Savannah K. Bertolli; Beth A. Shen; Uma Mitchell; Larry A. Gallagher; Matthew C. Radey; S. Brook Peterson; Joseph D. Mougous (Proceedings of the National Academy of Sciences, 2025)
Data suggest that antagonism between bacteria is prevalent within the gut microbiome. Such antagonism could have profound consequences on the fitness of species; however, the susceptibility determinants to even the most pervasive antagonistic factors in this ecosystem remain incompletely understood. Here, we screened for genetic factors that impact the susceptibility of Bacteroides to type VI secretion system (T6SS)-delivered toxins. This revealed that the Bte2 family of pore-forming toxins, which are widespread in B. fragilis and other human gut-associated Bacteroidales, strictly requires the H + /Na + -translocating ferredoxin:NAD + reductase (Rnf) electron transport chain within target cells in order to intoxicate. In Bacteroides , the precise metabolic role of the conserved Rnf pathway has not been defined. We establish that the Rnf complex is important for redox balancing within cells utilizing sugars derived from dietary fiber and is critical for fitness in vivo. Surprisingly, we find that while the intact Rnf membrane complex is required for Bte2 intoxication, Rnf-catalyzed electron transport is dispensable. We propose that the Rnf complex facilitates Bte2 membrane insertion, leading to intoxication via membrane depolarization. Our data suggest that T6SS toxins may avoid collateral damage within a complex ecosystem by recognizing discriminatory features of competitor species.